Mitigating Job Burnout in Community Supervisors: The Role of Psychological Capital and Organizational Support - Purnama Sriwahyuni; Fanny Martdianty (Green Publisher Indonesia, 2026)
Community Counselors (PK) play an important role in the implementation of the correctional system in Indonesia. The high demands of work, emotional pressure, and the complexity of the tasks faced by PK authentically increase the risk of job burnout, so a comprehensive understanding of the factors that can mitigate these conditions is needed. This study aims to analyze the influence of organizational support on job burnout by considering the mediating role of psychological capital and self-esteem in PK in Indonesia. This study employed a quantitative approach with a survey method using a 7-point Likert scale online questionnaire. Data were collected from 398 PK respondents, with 381 valid responses after data cleaning. Data were analyzed using SEM with LISREL. The results of the study show that organizational support has a negative effect on job burnout. In addition, psychological capital has been shown to play a significant role as a mediator in the relationship, while self-esteem also plays a mediator but with a relatively lower influence. These findings suggest that increasing organizational support not only directly reduces job burnout, but also indirectly through an increase in the psychological capacity of individuals. The implications of this study emphasize the importance of the role of organizations in creating adequate support and strengthening the psychological capacity of individuals to reduce the level of job burnout. This research is expected to contribute to the development of human resource policies, especially in the context of the public sector.